Latar Pendidikan Dewan Direksi, Dewan Komisaris, Komite Audit dan Praktik Manajemen Laba Riil - Andira, Mira Hasta; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi, 2022)
Earnings management is a form of opportunistic action taken by managers to achieve certain goals. The purpose of this study was to determine the effect of the educational background of the board of directors, board of commissioners and audit committee on real earnings management. This research was conducted in a manufacturing company listed on the Indonesia Stock Exchange (IDX) using purposive sampling method. The analysis technique used is multiple linear regression. Based on the results of the analysis, it was found that the educational background of accounting and finance owned by the board of directors, board of commissioners and audit committee had a negative effect on real earnings management in the company. The results also show that the educational background of accounting and finance is one of the factors that can prevent the occurrence of earnings management in the company. Keywords : Real Earning Management; Education; Board Of Director; Board Of Commissioner; Audit Committee.